Membership Protocols for the iTrust Network - Chuang, Yung Ting; Smith, Peter M. Melliar; Moser, Louise E; Lombera, Isai Michel (Discoveries in Agriculture and Food Sciences, 2015)
The iTrust system is a decentralized and distributed system for information publication, search and retrieval over the Internet, which is designed to make it difficult to censor or filter information. In this paper, we present four membership protocols for the iTrust network, namely, the non-adaptive, retry, adaptive and combined adaptive membership protocols. We compare the performance of these membership protocols, with respect to four performance metrics, namely, membership accuracy, match probability, response time and message cost, for various parameter values when the membership churn is high and when the membership is stable.